Manara - Lighting up the Globe, One Publication at a Time - Alenka Blatnik (14526866) (2025)
This poster will discuss the role of Manara - Qatar Research Repository, a multi-institutional model platform provided by Qatar National Library (QNL). It serves as a national Open Access (OA) repository aggregator and institutional repository, designed to publish, and share research outputs from Qatar-based institutions. Manara supports academic publishers, government organizations, non-profits, research institutions, and enterprises, advancing open science, knowledge dissemination, and the re-use of research outputs. OA repositories play a crucial role in the scholarly, academic, and research processes by enhancing accessibility, discoverability, findability, and the impact of research studies. Powered by Figshare for Institutions, Manara is a research data and sharing platform developed by Digital Science. Researchers can store, manage, and showcase various outputs, including conventional (journal contributions, reports, presentations, 3D models) and non-conventional (datasets, processes, workflows, software, and tools) research outputs. Integrated tools like Dimensions and Altmetrics provide insights into research impact and engagement. Manara also integrates with DataCite for DOI assignment, ensuring better data citation and discoverability, and Open Researcher and Contributor ID (ORCID) for author attribution and long-term bibliographic tracking. The Figshare platform provides an interface that accurately displays statistics of ingested data and allows administrators to generate user and system reports. A key feature of Manara is its digital preservation service, ensuring the long-term accessibility, integrity, and usability of OA research content. Since launching in November 2022, over 150 researchers have registered, publishing more than 8,000 items, with journal contributions being the most common type. To enhance discoverability, Manara’s published contributions are organized into dedicated groups on the Institutions page. In 2024, in collaboration with Hamad Bin Khalifa University, Manara introduced support for publishing Ph.D. theses and Masters and bachelor’s dissertations. Further data stewardship developments will encourage registered users to publish more preprints, research laboratory data, and fully developed datasets, to support research collaboration, innovation, and new discoveries. Other Information Poster was presented at: Libraries Thriving Together in an Open Ecosystem https://www.qnl.qa/en/libraries-lead-forum-2025 License: https://creativecommons.org/licenses/by/4.0/ Conference information: Libraries Lead Forum 2025 https://www.qnl.qa/en/libraries-lead-forum-2025/agenda